Lnc-mg is a long non-coding RNA that promotes myogenesis - Mu Zhu (Nature Portfolio, 2017)
Long non-coding mRNAs play important roles in muscle development and regeneration. Here the authors identify a long non-coding mRNA that promotes myogenesis by sequestering miR-125b, leading to increased expression of insulin-like growth factor 2.